2020
DOI: 10.4018/ijseus.2020010106
|View full text |Cite
|
Sign up to set email alerts
|

Serious Games Effect Analysis On Player's Characteristics

Abstract: “Serious games” refer to games that go beyond pure entertainment and promote learning. They are utilized within a variety of learning environments enabling students to acquire knowledge and skills, while they offer wide benefits. The authors' team measured and analyzed various factors related to the gameplay and educational content when 2D and 3D serious games are introduced in the educational process. The main objective focused on the correlation of the University students' views that were sharing common char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Besides demographic information (such as age, gender, scientific background, ICT and game-playing competence), respondents were asked to indicate their agreement to fifty-four statements in a five-point Likert-type scale (worded strongly agree to strongly disagree). Its reliability and factorial structure were tested and confirmed in previous studies (Fokides, Kaimara, Deliyannis, & Atsikpasi, 2019;Fokides, Atsikpasi, Kaimara, & Deliyannis, 2019a, 2019bKaimara, Fokides, Plerou, Atsikpasi, & Deliyannis, 2020). The questionnaire's items of the "Scale for Measuring the Learning Experience in Serious Games" are presented in the Appendix.…”
Section: Instrumentmentioning
confidence: 65%
See 2 more Smart Citations
“…Besides demographic information (such as age, gender, scientific background, ICT and game-playing competence), respondents were asked to indicate their agreement to fifty-four statements in a five-point Likert-type scale (worded strongly agree to strongly disagree). Its reliability and factorial structure were tested and confirmed in previous studies (Fokides, Kaimara, Deliyannis, & Atsikpasi, 2019;Fokides, Atsikpasi, Kaimara, & Deliyannis, 2019a, 2019bKaimara, Fokides, Plerou, Atsikpasi, & Deliyannis, 2020). The questionnaire's items of the "Scale for Measuring the Learning Experience in Serious Games" are presented in the Appendix.…”
Section: Instrumentmentioning
confidence: 65%
“…In order to evaluate UX, to examine the possible statistically significant differences among users and to record if users pay attention to different aspects of games according to their particular characteristics, the SGs' type (2D or 3D) and the quality of human-game interaction were taken into account. In our previous researches (Fokides, Kaimara, Deliyannis, & Atsikpasi, 2019;Fokides, Atsikpasi, Kaimara & Deliyannis, 2019a, 2019bKaimara, Fokides, Plerou, Atsikpasi, & Deliyannis, 2020), we concluded that twelve factors can be used for assessing SGs: immersion, enjoyment, perceived usefulness-knowledge improvement, perceived narratives' adequacy, perceived realism, perceived feedback's adequacy, perceived audiovisual adequacy, perceived relevance to personal interests, perceived goal's clarity, perceived ease of use, adequacy of the learning material and motivation. In the present study, learners' experience was evaluated via a questionnaire which examined the above factors (see Appendix).…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…DGBL is a combination of serious learning and interactive entertainment and could be seen as the new paradigm for education (de Freitas & Liarokapis, 2011 ; Prensky, 2007 ). Several studies provide measurable evidence that DGBL boosts learning outcomes (Clark et al, 2016 ; Fokides, 2020 ; Gee, 2008 ; Girard et al, 2013 ; Hamari et al, 2016 ; Hersh & Leporini, 2018 ; Kaimara et al, 2020 ). Although the evidence of DGBL effectiveness is strong, there are also those academic voices who claim that digital games are largely ineffective and ill-suited to school structure.…”
Section: Introductionmentioning
confidence: 99%
“…Undisputable fundamental factors in the educational process, i.e., teaching–learning, are teachers and learners. Authors’ previous studies examined learners’ views regarding digital educational games (Fokides et al, 2018 , 2019a , b ; Kaimara et al, 2019a , 2020a , b ). Regarding the role of teachers, it is concluded that there have been several studies on teachers' (pre-service and in-service) attitudes towards ICT integration in schools, and their willingness to use innovative technology but not a sufficient number of studies on their intention to integrate gaming literacy within educational goals in Greece (Megagianni & Kakana, 2021 ).…”
Section: Introductionmentioning
confidence: 99%